Integrated Metabolomic and Functional Assessment of Sexed Frozen Semen in Holstein Friesian Bulls - Yusuf, M.; Diansyah, A. M.; Sahiruddin, S.; Masturi, M.; Maulana, T.; Said, S.; Rahmat, R.; Alfian, A. M.; Adam, A. A. S.; Yusri, A. N. H. S.; Nurlatifah, A.; Amrullah, M. F. (Tropical Animal Science Journal, 2026)
This study examined the differences in sperm quality and metabolite profiles among X and Y sperm in Friesian Holstein bulls. It also tried to find specific metabolites that can help improve the accuracy of sexed semen use in humid tropical dairy farms. Semen samples from five bulls were separated by sex and tested for movement, live sperm count, shape, and membrane and acrosome health. The tests used Computer-Assisted Sperm Analysis (CASA) and regular microscope checks. Metabolite analysis was performed using LC-HRMS, followed by various statistical tests, pathway checks, and ROC curve analysis. The outcomes showed that X sperm had better movement and acrosome health, while Y sperm had stronger membranes, fewer shape problems, and moved faster. The untargeted metabolite study showed clear differences between the two groups. X sperm had more identified metabolites and greater average levels. The crucial metabolites found more in X sperm were D-(−)-fructose, L-(+)-lactic acid, and sn-glycero-3-phosphocholine. Meanwhile, Y sperm had greater levels of acetyl-L-carnitine. The pathway analysis showed that X sperm primarily utilized carbohydrate and fat processing through glycolysis and phosphocholine pathways to maintain their movement and membrane integrity. On the other hand, Y sperm mainly use a carnitine-based energy pathway to support their faster and straighter movement. The identified metabolites can serve as reliable biomarkers to aid in laboratory quality control checks and enhance the quality of semen extenders. This outcome gives a good way to make sexed semen more stable and reliable in tropical dairy farming conditions.